The formulation of the coastal resource management plan of Oton, Iloilo. - Fusin, Leslie
The study aimed to describe the CRM planning process of Oton, Iloilo in relation to the existing coastal management process being adapted for Philippine local government. It also determined the type of participation of subsistence fisher folks in the formulation of the Coastal Resource Management plan. The fisher folks' participation was determined through surveys, their types of participation were then categorized into Consultative Functional and Interactive type of participation. Coastal management is a long, detailed process. As a basic service of the local government, its benevolent aims equaled the weight of the procedure that needs to be followed. Dedication and patience should be greatly expended on the process of formulating plan. In order to enhance community participation as an ingredient of a successful CRM, proper value should be given to public education and awareness raising of the members of the community.